2017
DOI: 10.1186/s13075-017-1232-1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial injury in rheumatoid arthritis: a crosstalk between dimethylarginines and systemic inflammation

Abstract: BackgroundSymmetric (SDMA) and asymmetric (ADMA) dimethylarginines have emerged as novel biomarkers of cardiovascular disease (CVD) in several disease settings associated with atherosclerosis. Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease characterized by high CVD mortality and morbidity. ADMA and SDMA levels are abnormal in RA patients, but their correlation with assessments of endothelial function and structure remains unknown. We aimed to investigate whether SDMA and ADMA are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 40 publications
1
45
0
4
Order By: Relevance
“…In patients with high disease activity and no overt atherosclerotic disease or classic risk factors, high plasma ADMA levels significantly correlated with IMT [67], coronary flow reserve (CFR) [56], and pulse wave velocity (PWV) [58], whereas in those with evident atherosclerosis and CV risk factors, negative correlation between ADMA and FMD [65] and carotid IMT (cIMT) [62,68] was found. In the latter subgroup of patients also, a positive relation was observed between the ADMA : SDMA ratio (suggested as the index of dimethylarginine dimethylaminohydrolase activity) and microvascular endothelial function [68] and arterial stiffness [62]. However, these relationships were not observed in RA patients with low and moderate disease activities-although structural and functional changes in vessels and heart were detected by means of multiple noninvasive, validated methods including cIMT, FMD, CFR, PWV, laser Doppler, and subendocardial viability ratio (SEVR), no associations between dimethylarginines and assessments of vascular morphology and function were found [56,61,65].…”
Section: Asymmetric Dimethylarginine (Adma)mentioning
confidence: 98%
See 2 more Smart Citations
“…In patients with high disease activity and no overt atherosclerotic disease or classic risk factors, high plasma ADMA levels significantly correlated with IMT [67], coronary flow reserve (CFR) [56], and pulse wave velocity (PWV) [58], whereas in those with evident atherosclerosis and CV risk factors, negative correlation between ADMA and FMD [65] and carotid IMT (cIMT) [62,68] was found. In the latter subgroup of patients also, a positive relation was observed between the ADMA : SDMA ratio (suggested as the index of dimethylarginine dimethylaminohydrolase activity) and microvascular endothelial function [68] and arterial stiffness [62]. However, these relationships were not observed in RA patients with low and moderate disease activities-although structural and functional changes in vessels and heart were detected by means of multiple noninvasive, validated methods including cIMT, FMD, CFR, PWV, laser Doppler, and subendocardial viability ratio (SEVR), no associations between dimethylarginines and assessments of vascular morphology and function were found [56,61,65].…”
Section: Asymmetric Dimethylarginine (Adma)mentioning
confidence: 98%
“…Negative regulation of NO synthesis can also be mediated through overproduction of methylated arginine analogues such as ADMA. Recently, many clinical studies have demonstrated that plasma levels of ADMA were elevated in RA patients regardless of the presence of cardiovascular disease [55][56][57][58][59][60][61][62][63][64][65][66][67]. Furthermore, ADMA has been reported to be related to indices of endothelial dysfunction or subclinical atherosclerosis in some [56,65,68], but not all, conducted studies [58,60,61,67,68].…”
Section: Asymmetric Dimethylarginine (Adma)mentioning
confidence: 99%
See 1 more Smart Citation
“…This might account for the reduced coronary flow reserve, and consequent increased risk of ischaemic heart disease, reported in patients with rheumatoid arthritis and other similar autoimmune conditions [68]. In addition to the potential role of inflammatory pathways and traditional cardiovascular risk factors, the accumulation of the potent endogenous inhibitor of eNOS synthase, asymmetric dimethylarginine (ADMA), might also play a role in the pathogenesis of endothelial dysfunction in rheumatoid arthritis [69][70][71].…”
Section: Rheumatoid Arthritis: a Human Model Of Premature Vascular Agmentioning
confidence: 99%
“…(2017) у больных РА с умеренной и высокой активностью при высоком содержании С-реактивного белка и в значительной степени увеличенной скорости оседания эритроцитов были констатированы более низкие значения поток-зависимой вазодилатации эндотелия и более высокие концентрации циркулирующих маркёров ЭД. Это свидетельствовало об ухудшении функций эндотелия при нарастании активности воспаления у больных РА [25].…”
unclassified